SP5.2.5 A 4-year single-centre cohort study assessing outcomes in vascular surgery patients undergoing calf fasciotomies. (28th October 2021) - Laloo, Ryan; Bailey, Marc; Troxler, Max; Russell, David; Scott, David Julian Ashbridge
Abstract: Aims: Acute compartment syndrome (ACS) is a surgical emergency. Delayed diagnosis and fasciotomy can result in irreversible muscle necrosis causing permanent disability and major amputation. This study compared patient outcomes following calf fasciotomies to prevent ACS (prophylactic) versus treat ACS (therapeutic) and early (within 6 hours of ACS diagnosis) versus delayed fasciotomies (beyond 6 hours) at a single vascular centre. Methods: All patients undergoing calf fasciotomies between 1st January 2017 and 31 st December 2020 were identified from a prospectively collected departmental database. Caldecott-approved data collection was conducted. The primary outcomes were wound infection, foot drop, muscle debridement, split-skin graft (SSG) requirement, vacuum dressing, 30-day amputation and death rates. Statistical analysis was performed using Fisher's exact test. Results: 73 patients (51 men, 22 women; median age 67, IQR 56-75 years) underwent calf fasciotomies (44 therapeutic and 29 prophylactic) mainly following acute thromboembolic ischaemia. Higher complication rates occurred among delayed (15) versus early (29) fasciotomy patients: wound infection (13.3% vs 3.4%), foot drop (20.0% vs 3.4%), muscle debridement (40.0% vs 24.1%), loss of anterior compartment (13.3%, 3.4%) need for SSG (29.5% vs 17.2%), vacuum dressing (46.7% vs 20.7%) and 30-day amputation rate (20.0% vs 13.8%) but lower 30-day death rate 13.3% vs 17.2%). None of these results were statistically significant. 34.1% of delayed fasciotomies were due to awaiting emergency theatre availability. Conclusion: ACS patients undergoing calf fasciotomies are at high risk of complications including amputation and death. Ongoing education on mortality risk and early communication with emergency theatres are critical in their management.